Achievements in breeding cereals with durable disease resistance in Northwest Europe - Brown, James K. M. (Burleigh Dodds Series in Agricultural Science, 2021)
Breeding cereals in Northwest Europe for durable resistance has made an important contribution to control of almost all economically significant diseases and pests of wheat, barley and oats. Durable resistance to fungal diseases is largely polygenic and quantitative, with the important exception of mlo resistance to powdery mildew of spring barley. Resistance to powdery mildew of winter wheat, spring barley and spring oats, brown rust of winter barley and Septoria nodorum blotch of wheat has been especially effective and durable. Resistance to Barley yellow mosaic virus and orange wheat blossom midge has used single genes which have so far been durable. Plant breeders are increasingly producing varieties with high or moderate resistance to all the most important diseases, and have successfully combined durable resistance with other traits which are important to farmers and end-users, including high yield, marketable grain quality and desirable agronomic properties.